Overview Of The Process Of Utilizing Smart Tv Merah Putih In Stimulating The Cognitive Abilities Of Children In Group B At Satya Prawira PAUD - Alawiyah, Tuti (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The Smart TV Merah Putih, as one of the learning technology products in the Merdeka Belajar program, offers great potential in early childhood education. This research aims to describe the process of utilizing the Smart TV Merah Putih in stimulating the cognitive abilities of Group B children at PAUD Satya Prawira. The study uses a descriptive qualitative approach with a case study method. Data collection techniques were carried out through participant observation, in-depth interviews with teachers, and documentation of learning activities. The research subjects were 15 Group B children and 2 accompanying teachers. The results revealed that the utilization process of the Smart TV Merah Putih occurs in three main stages: (1) preparation (teachers select educational content from the Digital Aplikasi Sekolah Indonesia (DASI) and Merdeka Mengajar platforms that align with cognitive objectives), (2) implementation (screening animated videos, educational songs, and interactive games that stimulate memory, classification, problem-solving, and number concept recognition), and (3) reflection (teachers conduct Q&A and follow-up activities based on the viewing). This process successfully created engaging learning, increased children's focus and participation, and provided concrete visual-auditory experiences to develop cognitive abilities. The main challenges lie in internet connectivity and the need for teachers to adapt in integrating viewing with hands-on activities. It is concluded that the Smart TV Merah Putih, when supported by thorough teacher planning, can be an effective cognitive stimulation tool in building the logical and creative thinking foundation of early childhood.